Understanding the participation experience of the top contributors in a crowdsourcing of inventive activities context. (March 2017) - Innocent, Morgane; Gabriel, Patrick; Divard, Ronan
The aim of this research is to identify the dimensions of the lived experience of contributors in a crowdsourcing of inventive activities context. The study is based on 93 online interviews from three major crowdsourcing platforms with contributors who have won at least one contest. The results reveal a participation experience with six dimensions. In addition to the praxeological, hedonic-sensory, rhetorical and temporal dimensions, the participation experience also includes eudemonic and liberating components. The six dimensions observed are found to be combined in an experiential system, which is organised around cross-dimensional themes such as learning and social interaction. These results encourage the development of an experiential context that fosters the emergence of the six dimensions in order to enhance the richness, diversity and memorability of participation.